Intensive Grandmothering? Exploring the Changing Nature of Grandmothering in the Context of Changes to Parenting Culture. (February 2022) - Harman, Vicki; Cappellini, Benedetta; Webster, Michelle
This article explores the ways in which the intensification of parenting and the notion of children at risk have influenced grandmothers' narratives and practices. Interviews with grandmothers who regularly look after their grandchildren, reveal that their practices are framed around the notions of children to be protected, educated and entertained . Such notions reveal that aspects of grandmothers' roles as protectors, educators, playmates and confidants involved negotiations with parents around the ideal of 'putting the child first'. The article argues that intensive parenting has influenced grandmothering but the way this is enacted reveals resistance to certain aspects of intensive parenting.